The Introduction and Implementation of Digital Payments through QRIS for MSMEs in Kelurahan Suka Asih, Tangerang City to Realize a Green Economy as Part of Sustainable Indonesian Development - Triana Zuhrotun Aulia; Sudarmanto, Eko; Susilo, Priyo (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
This activity aims to increase understanding of digital-based payments using the Quick Response Code Indonesian Standard (QRIS) for MSMEs and the general public in Kelurahan Suka Asih, Tangerang City. This activity was carried out using seminar methods, socialization and assistance in the use of QRIS for MSMEs. The results of this community service activity show that the knowledge and understanding of residents about QRIS has an impact on the use of QRIS in the future. This community service activity, in addition to supporting the Tangerang City government program in growing a digital-based people's economy, also opens wider access for the community to financial services to encourage financial inclusion and reduce economic disparities in Tangerang City.